Public Opinion and Understanding of the Impact of Electric Vehicles: A UK Experience - Kennedy, Joshua; James, Kieran; Hampson, Bonnie (Advances in Social Sciences Research Journal, 2023)
The UK Government places pressure on the automotive industry to reduce carbon emissions by prioritising the manufacture of alternative fuel vehicles. Hence, electric vehicles (EVs) are a priority for the automotive industry given they emit minimal carbon emissions compared to petrol and diesel vehicles. Despite the continued improvement in the manufacture of EVs, issues regarding the viability and affordability of the vehicles influence the market for EVs. This paper explores opinions regarding (i) the viability and environmental impact of EVs as a replacement for petrol/diesel vehicles; (ii) the affordability of EVs; and (iii) knowledge and familiarity of the use of EVs. 130 respondents to a questionnaire, along with interviews with participants within the automotive industry inlcuding an owner of an EV, generally supported literature on the study of EVs. Findings of this research identified that views relating to the viability of EVs focussed on range anxiety, charging speeds and battery life. Views relating to the affordability of EVs are influenced by the initial purchase price of the vehicle, along with costs associated with the battery and charging point. Finally, it is clear that consumers with greater knowledge about EV technologies are more likely to embrace EVs.